Apakah Teori Perilaku Terencana Relevan Mengukur Perilaku Mahasiswa Dalam Mengelola Keuangan di Tahun Kedua Era Pandemi Covid-19? - Jarot Prasetyo; Anis Marjukah; Rismanto Gatot Trisilo; Cahaya Nugrahani; Syska Lady Sulistyowati; Anna Febrianty S (Journal of Business and Economics Research (JBE), 2022)
This study aims to test the model whether age, academic ability, working experence in the theory of Planned Behavior have a positive financial literacy and financial behavior of the students of Widya Dharma University during second year pandemi Covid-19. The research design was carried out using a quantitative method which explains the causal relationship between one dependent variable which is influenced by three independent variables and one mediating variable. Hypothesis testing is formulated in the model using the SEM analysist. The population in the research were all university students in the Unwidha Klaten in 6 faculties and 16 programmes of study. The sampling technique was carried out by purposive sampling as 140 respondents. The final result of the quantitative model test using AMOS stastical package shows that there is a positive influence on academic ability, working experience and financial literacy towards financial behaviors. Meanwhile, one variable in the age does not significantly influence it. Future research can expand the model through testing the students’s intellligence financial by developing research designs through experimental research.